Glycine zipper motifs in Hepatitis C virus nonstructural protein 4B are required for the establishment of viral replication organelles - Paul, David; Madan Renes, Vanesa; Ramirez, Omar; Bencun, Maja; Stoeck, Ina Karen; Jirasko, Vlastimil; Bartenschlager, Ralf (Journal of virology, 2018)
Hepatitis C virus (HCV) RNA replication occurs in tight association with remodeled host cell membranes, presenting as cytoplasmic accumulations of single-, double-, and multimembrane vesicles in infected cells. Formation of these so-called replication organelles is mediated by a complex interplay of host cell factors and viral replicase proteins. Of these, nonstructural protein 4B (NS4B), an integral transmembrane protein, appears to play a key role, but little is known about the molecular mechanisms of how this protein contributes to organelle biogenesis. Using forward and reverse genetics, we identified glycine zipper motifs within transmembrane helices 2 and 3 of NS4B that are critically involved in viral RNA replication. Foerster resonance energy transfer analysis revealed the importance of the glycine zippers in NS4B homo- and heterotypic self-interactions. Additionally, ultrastructural analysis using electron microscopy unraveled a prominent role of glycine zipper residues for the subcellular distribution and the morphology of HCV-induced double-membrane vesicles. Notably, loss-of-function NS4B glycine zipper mutants prominently induced single-membrane vesicles with secondary invaginations that might represent an arrested intermediate state in double-membrane vesicle formation. These findings highlight a so-far-unknown role of glycine residues within the membrane integral core domain for NS4B self-interaction and functional as well as structural integrity of HCV replication organelles. - IMPORTANCE Remodeling of the cellular endomembrane system leading to the establishment of replication organelles is a hallmark of positive-strand RNA viruses. In the case of HCV, expression of the nonstructural proteins induces the accumulation of double-membrane vesicles that likely arise from a concerted action of viral and coopted cellular factors. However, the underlying molecular mechanisms are incompletely understood. Here, we identify glycine zipper motifs within HCV NS4B transmembrane segments 2 and 3 that are crucial for the protein's self-interaction. Moreover, glycine residues within NS4B transmembrane helices critically contribute to the biogenesis of functional replication organelles and, thus, efficient viral RNA replication. These results reveal how glycine zipper motifs in NS4B contribute to structural and functional integrity of the HCV replication organelles and, thus, viral RNA replication.